Capability Assessment of IT Governance Using the 2019 COBIT Framework for the IT Business Consultant Industry - Brian Hardjadinata, Maximillian; Wiratama, Jansen (International Journal of Science, Technology & Management, 2023)
Most Indonesian businesses need help with business alignment with information technology. COBIT is one of the frameworks controlled by IT Governance. COBIT 2019, the most recent COBIT framework, assesses information technology governance and capability levels at PT Kwadran Lima, Indonesia. Capability is measured by interviews regarding COBIT operations using a specified process domain. The COBIT Design Toolkit was used to establish the process domains. The process domains acquired were APO12-Managed Risk, BAI10-Managed Configuration, and DSS03-Managed Problem. These three domains solve challenges at PT Kwadran Lima in Indonesia. The process domain was assessed through interviews using the RACI Chart. Following the collection of measurement results, suggestions are made based on the findings of the evaluation results. According to the findings, PT Kwadran Lima Indonesia is still at level 2 to reach level 3. As a result, a proposal is made to develop or design a team whose tasks and responsibilities are to plan and execute ways of collecting categorization and associated data analysis of Information Technology risk for the Company to achieve level 3.